Intravascular Lithotripsy for Vessel Preparation in Calcified Coronary Arteries Prior to Stent Placement ― Japanese Disrupt CAD IV Study 2-Year Results - Takahashi, Akihiko; Kawasaki, Tomohiro; Yamazaki, Seiji; Namiki, Atsuo; Saito, Shigeru; Nakamura, Shigeru; Shibata, Yoshisato; Otsuji, Satoru (Circulation Reports, 2023)
Background: Intravascular lithotripsy (IVL) delivers acoustic pressure waves to modify calcification to enhance vessel compliance and optimize stent deployment. The Disrupt CAD IV study enrolled patients with severe coronary artery calcification. The primary safety (30-day major adverse coronary events [MACE], 6.3%) and effectiveness (procedural success, 93.8%) endpoints were achieved. The present analysis evaluated the 2-year outcomes of the study.Methods and Results: Disrupt CAD IV (NCT04151628) was a prospective, single-arm, multicenter study designed for regulatory approval of the Shockwave Coronary C2IVL system in Japan. Angiographic outcomes were analyzed by an independent core laboratory and adverse events were adjudicated by a Clinical Events Committee. Kaplan-Meier analysis was performed for MACE (composite of cardiac death, MI or target-vessel revascularization [TVR]), target lesion failure (TLF: composite of cardiac death, TV-MI, and target lesion revascularization [TLR]), and stent thrombosis (ST). At 2 years, 62 subjects had completed follow-up. MACE occurred in 12.6% (cardiac death 0.0%, MI 6.3%, TVR 7.9%) and TLF occurred in 7.8% of patients, with both rates driven by non-Q-wave MI events (6.3%). TLR was 3.2%; no ST occurred through 2 years.Conclusions: Treatment with IVL in patients with severely calcified coronary lesions was associated with low rates of MACE, TLR, and ST at 2 years, demonstrating continued durable safety and effectiveness of coronary IVL in a Japanese population.